2021
DOI: 10.1002/cam4.4232
|View full text |Cite
|
Sign up to set email alerts
|

Association of marital status with stage and survival in patients with mycosis fungoides: A population‐based study

Abstract: BACKGROUNDMycosis fungoides (MF), characterized by a monoclonal proliferation of CD4-positive T cells, is the most common type of cutaneous T-cell lymphoma (CTCL) and constitutes almost 50% of all primary cutaneous lymphomas. 1 According to a newly published study, the incidence of MF increased from 3.0 per million person-years in the 1970s to 5.9 in the 2010s, 2 with a higher incidence in Blacks. 3 MF generally affects adult or elderly patients with a male-to-female ratio of 1.6-2.0:1. 1 Cases of children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Our findings suggested that divorced patients had more advanced disease stages at diagnosis, a finding that was also shown in patients with mycosis fungoides, lung neuroendocrine neoplasms, and melanoma 45–47 . There are several potential interpretations of this phenomenon.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our findings suggested that divorced patients had more advanced disease stages at diagnosis, a finding that was also shown in patients with mycosis fungoides, lung neuroendocrine neoplasms, and melanoma 45–47 . There are several potential interpretations of this phenomenon.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings suggested that divorced patients had more advanced disease stages at diagnosis, a finding that was also shown in patients with mycosis fungoides, lung neuroendocrine neoplasms, and melanoma. [45][46][47] There are several potential interpretations of this phenomenon. Physical examination of married patients is conducted regularly under the supervision of their spouses before being diagnosed, and married patients are more likely to be diagnosed at an earlier stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between marital status and better survival was found in two studies with patients with gastric cancer, 36,68 and in one study each on patients with epithelial ovarian, 66 esophageal, 53 colorectal, 67 liver, 69 renal, 71 thyroid, 58 kidney, 34 gallbladder, 60 endometrial, 82 head and neck, 83 breast, 32 rectal, 81 lung, 79 pancreatic 86 and laryngeal cancer 55 . The association was also found in one study each on patients with bladder urothelial carcinoma, 72 astrocytoma, 73 spinal cord tumours, 87 glioblastoma multiforme, 74 renal cell carcinoma, 76 cutaneous melanoma, 77 uveal melanoma, 54 laryngeal cancer, 55 lung adenocarcinoma 64 and mycosis fungoides, 50 and in one study on patients with various cancer types 85 …”
Section: Resultsmentioning
confidence: 78%
“…The sub‐category single versus married patients was compared in eight studies. All but two 50,51 reported that married patients had higher overall survival rates than single patients. The association was found in studies on patients with cervical, 52 esophageal, 53 uveal melanoma, 54 laryngeal cancer, 55 soft tissue sarcoma 56 and in one study with various cancer types 25 .…”
Section: Resultsmentioning
confidence: 99%